Effect of Perioperative Electroacupuncture as An Adjunctive Therapy on Postoperative Analgesia with Tramadol and Ketamine in Prostatectomy: A Randomised Sham-Controlled Single-Blind Trial. Issue 3 (June 2014) - Ntritsou, Vagia; Mavrommatis, Christos; Kostoglou, Christos; Dimitriadis, Georgios; Tziris, Nikolaos; Zagka, Poulcheria; Vasilakos, Dimitrios
Objectives: To study the analgesic effect of electroacupuncture (EA) as perioperative adjunctive therapy added to a systemic analgesic strategy (including tramadol and ketamine) for postoperative pain, opioid-related side effects and patient satisfaction. Methods: In a sham-controlled participant- and observer-blinded trial, 75 patients undergoing radical prostatectomy were randomly assigned to two groups: (1) EA (n=37; tramadol+ketamine+EA) and (2) control (n=38; tramadol+ketamine). EA (100 Hz frequency) was applied at LI4 bilaterally during the closure of the abdominal walls and EA (4 Hz) was applied at ST36 and LI4 bilaterally immediately after extubation. The control group had sham acupuncture without penetration or stimulation. The following outcomes were evaluated: postoperative pain using the Numerical Rating Scale (NRS) and McGill Scale (SF_MPQ), mechanical pain thresholds using algometer application close to the wound, cortisol measurements, rescue analgesia, Spielberger State Trait Anxiety Inventory (STAI Y-6 item), patient satisfaction and opioid side effects. Results: Pain scores on the NRS and SF_MPQ were significantly lower and electronic pressure algometer measurements were significantly higher in the EA group than in the control group (p<0.001) at all assessments. In the EA group a significant decrease in rescue analgesia was observed at 45 min (p<0.001) and a significant decrease in cortisol levels was also observed (p<0.05). Patients expressed satisfaction with the analgesia, especially in the EA group (p<0.01). Significant delays in the start of bowel movements were observed in the control group at 45 min (p<0.001) and 2 h (p<0.05). Conclusions: Adding EA perioperatively should be considered an option as part of a multimodal analgesic strategy.